Evaluation of health care utilisation and mortality in medical hospitalisations with multimorbidity and kidney disease, according to frailty: a nationwide cohort study (Swiss Medical Weekly, 2024)
INTRODUCTION: The impact of impaired kidney function on healthcare use among medical hospitalisations with multimorbidity and frailty is incompletely understood. In this study, we assessed the prevalence of acute kidney injury (AKI) and chronic kidney disease (CKD) among multimorbid medical hospitalisations in Switzerland and explored the associations of kidney disease with in-hospital outcomes across different frailty strata.METHODS: This observational study analysed nationwide hospitalisation records from 1 January 2012 to 31 December 2020. We included adults (age ≥18 years) with underlying multimorbidity hospitalised in a medical ward. The study population consisted of hospitalisations with AKI, CKD or no kidney disease (reference group), and was stratified by three frailty levels (non-frail, pre-frail, frail). Main outcomes were in-hospital mortality, intensive care unit (ICU) treatment, length of stay (LOS) and all-cause 30-day readmission. We estimated multivariable adjusted odds ratios (OR) and changes in percentage of log-transformed continuous outcomes with 95% confidence intervals (CI).RESULTS: Among 2,651,501 medical hospitalisations with multimorbidity, 198,870 had a diagnosis of AKI (7.5%), 452,990 a diagnosis of CKD (17.1%) and 1,999,641 (75.4%) no kidney disease. For the reference group, the risk of in-hospital mortality was 4.4%, for the AKI group 14.4% (adjusted odds ratio [aOR] 2.56 [95% CI 2.52–2.61]) and for the CKD group 5.9% (aOR 0.98 [95% CI 0.96–0.99]), while prevalence of ICU treatment was, respectively, 10.5%, 21.8% (aOR 2.39 [95% CI 2.36–2.43]) and 9.3% (aOR 1.01 [95% CI 1.00–1.02]). Median LOS was 5 days (interquartile range [IQR] 2.0–9.0) in hospitalisations without kidney disease, 9 days (IQR 5.0–15.0) (adjusted change [%] 67.13% [95% CI 66.18–68.08%]) in those with AKI and 7 days (IQR 4.0–12.0) (adjusted change [%] 18.94% [95% CI 18.52–19.36%]) in those with CKD. The prevalence of 30-day readmission was, respectively, 13.3%, 13.7% (aOR 1.21 [95% CI 1.19–1.23]) and 14.8% (aOR 1.26 [95% CI 1.25–1.28]). In general, the frequency of adverse outcomes increased with the severity of frailty.CONCLUSION: In medical hospitalisations with multimorbidity, the presence of AKI or CKD was associated with substantial additional hospitalisations and healthcare utilisation across all frailty strata. This information is of major importance for cost estimates and should stimulate discussion on reimbursement.